(untitled) (JOURNAL OF ADVANCES IN PHYSICS, 2018)
This paper points out that not only all quantum-ghost puzzles occur in the Time Quantum Worm Hole, but also the dark matter in the universe is hidden in it. Dark energy is the contribution of the Planck black hole left behind by the early universe.